DAMPAK MARAKNYA BANK KELILING ( BANK EMOK ) DI KALANGAN MASYARAKAT BUNGURSARI KOTA TASIKMALAYA - Hasna Gustiani Wahidah; Matnur Ritonga (Bajang Institute, 2023)
Emok Bank is a term for a microfinance business that lends money to the public using a group lender system that is done every week. The existence of emok bank in Bungursari, Bungursari Village, Bungursari District, Tasikmalaya City is used by the community as one of the supports for economic activity. Emok Bank provides an easy loan process that is carried out. This is what makes the emok bank still have an existence in the midst of the many financial sectors, both formal and informal, that are offered in Bungursari Village. The aim of the research was to find out the mechanism of emok bank loans in Bungursari Village, Bungursari Village, Bungursari District, Tasikmalaya City and what kind of social impact was felt by the Bungursari community. As well as to find out the actions of the local government in an effort to eradicate Bank Emok. The results of the study explained that the people of Bungursari Village, Bungursari Village, Bungursari District, Tasikmalaya City carried out a loan mechanism at the emok bank through several stages. The community also has dependence on emok banks due to economic factors and administrative aspects as well as changes in social and economic conditions that reduce living standards. Bank emok has been considered as the easiest initial alternative in lending. The selection was also based on how many people practice loans at emok banks. This is what ultimately causes loans to emok banks to be considered normal. The emok bank in Bungursari Village seems to have become an alternative to support the community's economic needs. The local government has also taken preventive measures to eradicate the emok bank by holding joint deliberations and forming community programs such as cooperatives.